A survey: issues and challenges in wireless sensor network - Bala, Tarun; Bhatia, Varsha; Kumawat, Sunita; Jaglan, Vivek (International Journal of Engineering and Technology, 2018)
Wireless Sensor Network (WSN) is powerful and economical key to monitoring and tracking problems. WSN is a perfect unification of sensing, computation and communications tasks. WSN nodes are deployed in both hostile and harsh environment. They lend valuable support for continuous, remote monitoring, and for healthcare applications. WSN nodes can be deployed easily in existing structures without any added infrastructure. In this work, an outline of wireless sensor networks, applications, challenges & issues involved in implementing them is presented.